2022
DOI: 10.1002/adfm.202203081
|View full text |Cite
|
Sign up to set email alerts
|

A “Two‐in‐One” Strategy for Flexible Aqueous Batteries Operated at −80 °C

Abstract: The development of aqueous metal-ion batteries has attracted great attention due to their relatively low cost and high safety levels. However, their practical applications are hindered by the ease at which their aqueous electrolytes freeze. Inspired by the antifreezing properties of salts and alcohol cryoprotective agents, a "two-in-one" cryoprotective agent, hydroxyl-functionalized poly( ionicliquid) (PIL-OH)-based hydrogel electrolyte for aqueous lithiumion batteries (ALIBs) is developed. The synergy of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 51 publications
(77 reference statements)
0
41
0
2
Order By: Relevance
“…Lithium metal batteries (LMBs) have high energy densities and thus are considered as the most promising next-generation battery system to use in daily-life applications. Ni-rich ternary electrodes, which have high gram capacity and operating voltages and are cost-effective and nontoxic, are used for the fabrication of LMBs with high energy densities. However, Ni-rich cathodes have poor structural and compositional stability and are sensitive to HF and H 2 O in electrolytes. Therefore, transition metal ions are leached, and unstable interfacial structures are formed in the cathode and anode, thereby limiting the practical applicability of Ni-rich cathodes …”
Section: Introductionmentioning
confidence: 99%
“…Lithium metal batteries (LMBs) have high energy densities and thus are considered as the most promising next-generation battery system to use in daily-life applications. Ni-rich ternary electrodes, which have high gram capacity and operating voltages and are cost-effective and nontoxic, are used for the fabrication of LMBs with high energy densities. However, Ni-rich cathodes have poor structural and compositional stability and are sensitive to HF and H 2 O in electrolytes. Therefore, transition metal ions are leached, and unstable interfacial structures are formed in the cathode and anode, thereby limiting the practical applicability of Ni-rich cathodes …”
Section: Introductionmentioning
confidence: 99%
“…Since the first synthesis of quaternary ammonium salts by Jocobs et al in 1915, its antibacterial properties have been gradually discovered, which is also the first proposal of generalized poly (ionic liquids) (PILs) antibacterial agents [ 21 , 22 ]. The antibacterial mechanism is the positively charged ionic liquids (ILs) that attract the negatively charged bacterial cell walls through the anion–cation interactions [ 23 , 24 ]. Imidazolium PILs are one of the most widely used ILs, which have potent broad-spectrum bactericidal activity and slight cell toxicity [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although GOQDs can increase the temperature at which ice crystals appear during cooling, the DSC results during heating showed that the melting enthalpy decreased with the addition of GOQDs, indicating that the addition of GOQDs reduced the amount of ice crystallization. The water content and the non‐freezing water content could be calculated as follows: [21] normalWfs%=ΔHΔHm,4ptnormalH2normalO×100% $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {{\rm W}}_{fs}\left({\rm \char37 }\right)={{{\rm \Delta }H}\over{{\Delta H}_{m,{\rm \ }{\rm H}2{\rm O}}^{^\circ{}}}}\times 100\hskip0.17em\char37 \hfill\cr}}$ normalWnfs%=1-normalWfs $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {{\rm W}}_{nfs}\left(\char37 \right)=1-{{\rm W}}_{fs}\hfill\cr}}$ …”
Section: Resultsmentioning
confidence: 99%